Non-endoscopic management of a giant ureterocele: a case report in resource poor African hospital - Tela, Usman Mohammed; Olajide, Babatunde David; Lawan, Abdu Mohammed (International Surgery Journal, 2020)
Ureterocele is a cystic dilatation of the distal sub mucosal part of the ureter. It is a congenital anomaly that may co-exist with other anomalies. It has an incidence 1 in 4000 live births. Patients present with symptoms at paediatric age or may remain asymptomatic till adulthood. Our 30 year old female patient was assessed for a giant orthotropic right ureterocele with obstructive uropathy, in a hospital that has no modern facilities for endoscopic treatment. She then had successful open surgical repair of the ureterocele with satisfactory outcome. Minimally invasive endoscopic treatment options remains the gold standard. Patients from poor resource regions can as well be treated successfully by open surgical repair like our index case presented.